Cost-Benefit Analysis of Environmental Regulations and Corporate Compliance in Indonesia: A Law and Economics Approach - La Ode Muhammad Ihsan; Febi Melati Arum Dharu (The Indonesian Journal of Economic Analysis of Law, 2026)
Environmental regulations are designed to address negative externalities generated by industrial activities. This study evaluates environmental regulations in Indonesia through the lens of law and economics, emphasizing cost-benefit analysis as a tool for assessing regulatory effectiveness. The research investigates whether existing environmental laws create incentives for corporate compliance while maximizing social welfare. By applying economic theories of externalities, deterrence, and regulatory efficiency, the study examines the balance between environmental protection and economic development. The findings suggest that well-designed environmental regulations generate significant social benefits through pollution reduction, public health improvement, and environmental sustainability. Nevertheless, excessive compliance costs may reduce business competitiveness and discourage investment. The study argues that environmental policies should be structured to internalize external costs without imposing disproportionate burdens on economic actors. Market-based instruments, such as pollution taxes and emissions trading mechanisms, are identified as efficient alternatives to purely command-and-control regulations. Furthermore, legal certainty and effective enforcement are essential for ensuring compliance and minimizing transaction costs. The paper concludes that economic analysis provides valuable insights for designing environmental regulations that achieve both ecological and economic objectives. The findings offer practical implications for policymakers seeking to improve environmental governance while maintaining economic growth in Indonesia.